Herbicides to Kill Invasive Trees in Home Landscapes and Surrounding Natural Areas - Kenneth Langeland; Stephen F. Enloe (EDIS, 2016)
Several plant species that are invasive in natural areas of public lands also occur on private property. Invasive plants on private property that thrive within both landscaped and surrounding natural areas can serve as a source of infestation to other natural areas. Therefore, property owners are encouraged to remove invasive plant species from both areas. This 5-page fact sheet is a major revision that discusses different herbicides, hand-pulling, stump grinding, foliar herbicide application, cut stump herbicide application, basal bark herbicide application, hack-and-squirt, frill, or girdle herbicide application, licenses and training, and control of specific invasive plants. Written by K. A. Langeland and S. F. Enloe, and published by the UF Agronomy Department, May 2016.